Small Cell Carcinoma of Ovary, Hypercalcemic Type (Malignant Rhabdoid Tumor of Ovary) with Loss of SMARCA4 (BRG1) Expression: Report of Two Cases - Ayushi SAHAY; Katha KANTE; Santosh MENON; Jaya GHOSH; Rajendra A. KERKAR; Kedar K. DEODHAR (Türk Patoloji Dergisi, 2020)

(untitled)
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) / malignant rhabdoid tumor of the ovary (MRTO) is a rare tumor affecting young women. It is frequently misdiagnosed due to overlapping morphological and immunohistochemical features with many other ovarian tumors. The prognosis of the tumors is very poor; hence an accurate diagnosis is of utmost importance. Recently, the loss of BRG1 protein by immunohistochemistry has been shown to be a useful diagnostic marker. We present here two cases of SSCOHT/MRTO, in young women 22 and 32 years of age, where several differential diagnoses were considered on morphology and immunohistochemistry but were confirmed as SCCOHT/MRTO by the demonstration of loss of BRG1. As the prognosis of SCCOHT is very dismal, and accurate diagnosis is of necessity, we recommend the inclusion of BRG1 immunohistochemistry in the diagnostic armamentarium of poorly differentiated ovarian tumors, particularly in young adults.